1973
DOI: 10.6028/jres.077a.023
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of random copolymers

Abstract: A theory of crystallization is formulated for random copolymers which crystallize with the noncrystallizable co-units incorporated into the crystalline lattice as defects. The appropriate melting point equation and other associated thermodynamic properties are derived for this model as a function of crystal thickness and comonomer concentration. The formation of lam ellar type morphology is assumed to be a kinetically determined phenomena and nucleation theory is utilized accordingly. The isothermal lamella th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(67 citation statements)
references
References 11 publications
1
66
0
Order By: Relevance
“…Parameter value (estimated standard error) A = 68.0 (7.3) B = 84.5 (wt %)-I (37) C = 76900 (18800) UY/R = 675 K (64) y = 267 K (22) Kg = 535000 K2 (54000) Figure 5 shows predicted versus measured rate constants for the samples in this study. The agreement over a wide range of rates is satisfactory and this model can be used to predict crystallization rates for a range of optical composition, talc levels, and temperatures.…”
Section: Modelmentioning
confidence: 99%
“…Parameter value (estimated standard error) A = 68.0 (7.3) B = 84.5 (wt %)-I (37) C = 76900 (18800) UY/R = 675 K (64) y = 267 K (22) Kg = 535000 K2 (54000) Figure 5 shows predicted versus measured rate constants for the samples in this study. The agreement over a wide range of rates is satisfactory and this model can be used to predict crystallization rates for a range of optical composition, talc levels, and temperatures.…”
Section: Modelmentioning
confidence: 99%
“…The ®rst, proposed by Flory, 6 assumes that the comonomeric units B are not included in crystallites but remain in the amorphous phase. According to the second model, developed by Eby,7,8 there is full compatibility between the monomers of both types, ie comonomer B together with A build up the crystalline lattice. Wegner 9 compared the two models and concluded that they merely represent two extreme cases.…”
Section: Results and Discussion Characterization Of Copolyestersmentioning
confidence: 99%
“…We saw from growth rate measurements that the regio-defects have a more pronounced influence on the crystallization rate as compared to the stereo-defects. In order to obtain a better understanding of the influence of the amount and different types of defects on the growth rate we analysed our data with a theory originally developed by Lauritzen and Hoffman (LH-theory) [41,42], and later modified by Sanchez and Eby [22,23]. Although the LH-theory served as the basis for the derivation the theory, the final result will be independent of the exact molecular mechanisms (and thus the molecular background for the theory) involved for the particular case studied.…”
Section: Discussionmentioning
confidence: 99%
“…A discussion about the origin of the growth rate difference between the !-and "-phase as function of defect fraction is provided. Results obtained from the crystallization experiments are analyzed with the theory of Sanchez and Eby [22,23].…”
mentioning
confidence: 99%